Multilateral rules on competition policy : an overview of the debate - Paasman, Berend R. (ECLAC SantiagoCL, 1999)
Reviews the current debate on competition policy. Describes the different domestic compeetition policies in the United States, Europe and Latin American countries. Looks at the rationale for multilateral rules on competition policy and reviews previous attempts to establish multilateral competition policies. Outlines the current discussions at WTO with emphasis on the negotiating positions of the United States, the European Union and developing countries. Discusses issues that could be important to the formulation of a negotiating position for Latin American and Caribbean countries.